2012
DOI: 10.46582/jsrm.0803009
|View full text |Cite
|
Sign up to set email alerts
|

Non-Viral Generation of Neural Precursor-like Cells from Adult Human Fibroblasts

Abstract: Recent studies have reported direct reprogramming of human fibroblasts to mature neurons by the introduction of defined neural genes. This technology has potential use in the areas of neurological disease modeling and drug development. However, use of induced neurons for large-scale drug screening and cell-based replacement strategies is limited due to their inability to expand once reprogrammed. We propose it would be more desirable to induce expandable neural precursor cells directly from human fibroblasts. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(4 citation statements)
references
References 52 publications
(90 reference statements)
0
4
0
Order By: Relevance
“…Transdifferentiation has previously been carried out using fibroblasts or peripheral blood mononuclear cells (PBMCs) to neural stem cells, neurons, astrocytes, oligodendrocytes, microglia, and skeletal muscle cells ( Table 1 ). Direct differentiation is not limited to a terminally differentiated endpoint; for neurogenesis, reprogramming of fibroblasts to multipotent neural precursor cells can be performed with the overexpression of transcription factors SOX2, OCT3, KLF4, and MYC ( Meyer et al, 2014 ), SOX2 and PAX6 ( Maucksch et al, 2012 ), or even a single transcription factor, such as PTF1A ( Xiao et al, 2018 ).…”
Section: Recent Advances In Transdifferentiation Of Fibroblasts or Bl...mentioning
confidence: 99%
“…Transdifferentiation has previously been carried out using fibroblasts or peripheral blood mononuclear cells (PBMCs) to neural stem cells, neurons, astrocytes, oligodendrocytes, microglia, and skeletal muscle cells ( Table 1 ). Direct differentiation is not limited to a terminally differentiated endpoint; for neurogenesis, reprogramming of fibroblasts to multipotent neural precursor cells can be performed with the overexpression of transcription factors SOX2, OCT3, KLF4, and MYC ( Meyer et al, 2014 ), SOX2 and PAX6 ( Maucksch et al, 2012 ), or even a single transcription factor, such as PTF1A ( Xiao et al, 2018 ).…”
Section: Recent Advances In Transdifferentiation Of Fibroblasts or Bl...mentioning
confidence: 99%
“…In 2012, we reported the generation of iNPs from adult human fibroblasts using SOX2 and PAX6 cDNA plasmids or SOX2 and PAX6 recombinant protein expression [ 131 ]. Plasmid-derived iNPs expressed SOX2, PAX6, ASCL1, and NGN2 mRNA and protein, as well as the neural markers SOX1 , HOXB9 , NKX6.1 , and SIX3 .…”
Section: Direct Cell Reprogramming To Model Huntington’s Diseasementioning
confidence: 99%
“…iNPs differentiated into both GABAergic and glutamatergic neurons and a small proportion of astrocytes within 30 days and exhibited neuronal functionality. However, the reprogramming efficiency was low (0.05%), and the duration was 85 days long [ 131 ]. In 2018, our research group reported the generation of iNPs from adult human fibroblasts with a higher reprogramming efficiency (0.3%) and shorter time frame (21–28 days) following the transient expression of chemically-modified mRNA (cmRNA) encoding SOX2 and PAX6 [ 132 ].…”
Section: Direct Cell Reprogramming To Model Huntington’s Diseasementioning
confidence: 99%
“…We have developed a novel protocol that utilizes stable and non-immunogenic, chemically modified mRNA (cmRNA) to convert adult HDF to induced dorsal forebrain precursor cells (hiDFPs; Edwards et al, 2022 ). By transiently over-expressing the neural genes SOX2 and PAX6 using cmRNA we can generate hiDFPs which can subsequently be differentiated into cortical neurons (Maucksch et al, 2012 ; Connor et al, 2018 ; Playne et al, 2018 ; Edwards et al, 2022 ). Following 21 days of reprogramming, we have demonstrated that hiDFPs express the dorsal forebrain markers FOXG1, NGN2, BRN2, TBR1, TBR2, DLX2, CTIP2 , and SATB2 (Edwards et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%